Performance Comparison of the Taiwanese Independent and the Foreign Banks Before and After 2002 - Lin, Po Yang (2007)
The main purpose of this dissertation is to determine whether the establishment of Financial Holding Corporations (FHCs) and accession of WTO in 2002 affect the performance of independent and local branches of foreign banks in Taiwan. The research assessed 19 independent and 22 foreign banks from 1999 to 2006. The inputs and outputs are defined according to the intermediation approach. Inputs adopted in this dissertation are deposits, personnel expenses and fixed assets. Outputs are loans, other earning assets and non-interests income.